Methods for formation trajectories of motion of unmanned aircraft vehicles when flying around specified areas of space - A. Y. Bumai (Системный анализ и прикладная информатика)
The article analyzes various methods for constructing motion trajectories of unmanned aerial vehicles (UAVs) when flying over specified areas of space. The analytical results of the studies are presented in the form of qualitative illustrations of the methods under consideration, as well as the proposed methodology for forming an optimal UAV flight trajectory along the boundaries of a given area of space, taking into account the corresponding processes of changing the control acceleration and speed of the UAV and allowing the formation of requirements for the UAV control system at the preliminary development stage. An analysis of methods for forming UAV trajectories is carried out, on the basis of which a conclusion is made about the operability of the proposed methodology for forming the optimal UAV trajectory when flying over a given area of space and the feasibility of its further use as the basis for the initial stage of synthesis of the UAV control system.